Time-efficient method for the kinetic characterization of iron ore feedstocks for H2-based direct reduction - Michael Gallwitz; Jafet Roth; Robin Breitbach; Matthias Jahn; Gregor Herz; Erik Reichelt (Journal of Cleaner Production, 2025)

Wild Australian magpies learn to pull intact, not broken, strings to obtain food - Robin D. Johnsson; Papillon S. Veillet; Farley Connelly; John A. Endler; Timothy C. Roth; John A. Lesku (Behavioral Ecology and Sociobiology, 2023)
The string-pulling paradigm is an approach commonly used in the study of animal cognition to investigate problem-solving abilities. This test involves an out-of-reach reward that can only be acquired through pulling a string. Australian magpies ( Gymnorhina tibicen tyrannica ) can solve cognitive tasks requiring associative and reversal learning, spatial memory, and inhibitory control. Nonetheless, whether magpies can pass a test of means-end understanding—the string-pull test—is unclear. We tested wild magpies on a string-pulling task with five configurations, including a long loose string that required several pulls to obtain food, a short string that only required a single pull to complete, and two short strings—one intact and connected to the food reward; the other broken and unable to yield food when pulled. Of the 11 magpies tested, none solved the long string task at first presentation. Two naïve birds and three, subsequently trained, birds succeeded at the short string. Once proficient at the short string, four of these five birds then solved the long string task; in addition, three learned to choose a functional, intact string over a non-functional, broken string. Overall, these observations provide evidence that Australian magpies have the ability to solve string-pulling tasks but it remains unclear whether they do so by trial-and-error or if they possess means-end understanding. Significance statement We found, for the first time, that wild, free-ranging Australian magpies can learn to solve different versions of a string-pulling task; a version with a short string, a long string, and two strings next to each other where one of them was broken and non-functional (broken string task). Some magpies spontaneously solved the task with the short string, where other magpies required training, and magpies only managed to solve the task with the long string after they had succeeded on the short string task. Furthermore, some of the magpies solved the broken string task but required a high number of trials to do so. Overall, our findings show that Australian magpies have the ability to solve string-pulling tasks but it remains unclear whether they do so by trial-and-error or if they understand causal relations between objects.

Mainstreaming the social sciences in conservation - Nathan J. Bennett; Robin Roth; Sarah C. Klain; Kai M. A. Chan; Douglas A. Clark; Georgina Cullman; Graham Epstein; Michael Paul Nelson; Richard Stedman; Tara L. Teel; Rebecca E. W. Thomas; Carina Wyborn; et al. (Conservation Biology, 2017)
Despite broad recognition of the value of social sciences and increasingly vocal calls for better engagement with the human element of conservation, the conservation social sciences remain misunderstood and underutilized in practice. The conservation social sciences can provide unique and important contributions to society's understanding of the relationships between humans and nature and to improving conservation practice and outcomes. There are 4 barriers—ideological, institutional, knowledge, and capacity—to meaningful integration of the social sciences into conservation. We provide practical guidance on overcoming these barriers to mainstream the social sciences in conservation science, practice, and policy. Broadly, we recommend fostering knowledge on the scope and contributions of the social sciences to conservation, including social scientists from the inception of interdisciplinary research projects, incorporating social science research and insights during all stages of conservation planning and implementation, building social science capacity at all scales in conservation organizations and agencies, and promoting engagement with the social sciences in and through global conservation policy‐influencing organizations. Conservation social scientists, too, need to be willing to engage with natural science knowledge and to communicate insights and recommendations clearly. We urge the conservation community to move beyond superficial engagement with the conservation social sciences. A more inclusive and integrative conservation science—one that includes the natural and social sciences—will enable more ecologically effective and socially just conservation. Better collaboration among social scientists, natural scientists, practitioners, and policy makers will facilitate a renewed and more robust conservation. Mainstreaming the conservation social sciences will facilitate the uptake of the full range of insights and contributions from these fields into conservation policy and practice.

Generation of Priority Research Questions to Inform Conservation Policy and Management at a National Level - MURRAY A. RUDD; KAREN F. BEAZLEY; STEVEN J. COOKE; ERICA FLEISHMAN; DANIEL E. LANE; MICHAEL B. MASCIA; ROBIN ROTH; GARY TABOR; JISELLE A. BAKKER; TERESA BELLEFONTAINE; DOMINIQUE BERTEAUX; BERNARD CANTIN; et al. (Conservation Biology, 2011)
Integrating knowledge from across the natural and social sciences is necessary to effectively address societal tradeoffs between human use of biological diversity and its preservation. Collaborative processes can change the ways decision makers think about scientific evidence, enhance levels of mutual trust and credibility, and advance the conservation policy discourse. Canada has responsibility for a large fraction of some major ecosystems, such as boreal forests, Arctic tundra, wetlands, and temperate and Arctic oceans. Stressors to biological diversity within these ecosystems arise from activities of the country's resource‐based economy, as well as external drivers of environmental change. Effective management is complicated by incongruence between ecological and political boundaries and conflicting perspectives on social and economic goals. Many knowledge gaps about stressors and their management might be reduced through targeted, timely research. We identify 40 questions that, if addressed or answered, would advance research that has a high probability of supporting development of effective policies and management strategies for species, ecosystems, and ecological processes in Canada. A total of 396 candidate questions drawn from natural and social science disciplines were contributed by individuals with diverse organizational affiliations. These were collaboratively winnowed to 40 by our team of collaborators. The questions emphasize understanding ecosystems, the effects and mitigation of climate change, coordinating governance and management efforts across multiple jurisdictions, and examining relations between conservation policy and the social and economic well‐being of Aboriginal peoples. The questions we identified provide potential links between evidence from the conservation sciences and formulation of policies for conservation and resource management. Our collaborative process of communication and engagement between scientists and decision makers for generating and prioritizing research questions at a national level could be a model for similar efforts beyond Canada.

Ultrastructure of the membrane systems in the unicellular cyanobacterium Synechocystis sp. strain PCC 6803 - Michelle Liberton; R. Howard Berg; John Heuser; Robin Roth; Himadri B. Pakrasi (Protoplasma, 2006)